Multiple actor orientation: A case study of groundnut in Anantapur, Andhra Pradesh - Prasad, V.L.; Bezkorowajnyj, P.G.; Nigam, S.N.; Hanson, Jean; Romney, Dannie L. (SAGE Publications, 2011)
As part of a three-year project focusing on improving the livelihoods of poor livestock keepers by improving the availability of fodder, new groundnut varieties were tested, incorporating participatory rural appraisal (PRA), rapid rural appraisal (RRA), focus group discussions (FGDs) and field days as learning platforms. These approaches had limitations in addressing the complexity of the groundnut farming system and therefore constraints to the uptake of improved varieties continued to elude solution. The potential of a multi-stakeholder approach to gain a broader view of how novelty and innovation occur in a farming system was then recognized. Interactions among a range of actors including, among others, traders, oilseed merchants and private seed companies, were facilitated within a process of action and reflective learning. As a result, new constraints to innovation in groundnut varieties were identified and ways of overcoming them were noted. Documentation and analysis of the type and quality of linkages between the actors in the system helped to catalogue the process, and the platform thus created provided the actors with an opportunity to learn from each other. The lessons and implications are discussed.